1996
DOI: 10.1901/jeab.1996.65-423
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time and Choice in Concurrent Foraging Schedules

Abstract: Five pigeons were trained on a concurrent-schedule analogue of the "some patches are empty" procedure. Two concurrently available alternatives were arranged on a single response key and were signaled by red and green keylights. A subject could travel between these alternatives by responding on a second yellow "switching" key. Following a changeover to a patch, there was a probability (p) that a single reinforcer would be available on that alternative for a response after a time determined by the value of lambd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These ''overstaying'' results were replicated with pigeons by Davison and McCarthy (1994) and McCarthy, Voss, and Davison (1994). Jones and Davison (1996) introduced a concurrent variant of the ''some patches are empty'' procedure in which two discriminated patches were available, with potentially different times to reinforcers (preyarrival times) and different probabilities of reinforcers in the two patches. Despite the increased complexity of the task, their results closely replicated the results of Kamil et al, Davison and McCarthy, and McCarthy et al Brunner, Kacelnik, and Gibbon (1992) reported results from a modified procedure in which up to four prey items could be obtained on a single entry to a patch, each scheduled on equal successive fixed-interval (FI) schedules and terminating in a prey-absent trial.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…These ''overstaying'' results were replicated with pigeons by Davison and McCarthy (1994) and McCarthy, Voss, and Davison (1994). Jones and Davison (1996) introduced a concurrent variant of the ''some patches are empty'' procedure in which two discriminated patches were available, with potentially different times to reinforcers (preyarrival times) and different probabilities of reinforcers in the two patches. Despite the increased complexity of the task, their results closely replicated the results of Kamil et al, Davison and McCarthy, and McCarthy et al Brunner, Kacelnik, and Gibbon (1992) reported results from a modified procedure in which up to four prey items could be obtained on a single entry to a patch, each scheduled on equal successive fixed-interval (FI) schedules and terminating in a prey-absent trial.…”
mentioning
confidence: 88%
“…Ϯ15 g of their ad lib body weights. The subjects were the same as those used by Jones and Davison (1996). The subjects were fed amounts of mixed grain, immediately after sessions, sufficient to maintain their designated body weights.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations